Effects of Herbal Extracts Towards Microbicidal Activity Against Pathogenic Escherichia coli in Poultry - Asgari, Q.; Farzaneh, A.; Kalantari, M.; Mohajeri, F. Akrami; Moazeni, M.; Zarifi, M.; Esmaeilzadeh, B.; Motazedian, M.H. (International Journal of Poultry Science, 2006)
A total number of five plants were tested qualitatively to the presence of microbicidal activity by Kirby-Bour method in agar gel plates using poultry pathogenic E. coli as microbes. Among the five herbs used two herbs namely Piper betal and Cassia auriculata found to have microbicidal activity. The potency of microbicidal activity of that two herbs were tested quantitatively by the same method by using different dilutions and in different solvents, clinical experiments conducted in birds with infection and found that the plant Cassia auriculata have had more potent microbicidal activity when compare to Piper betel and screened for side effects, additional effects in birds.